Analisis Pengaruh Teori Vygotsky terhadap Pembelajaran Matematika Serta Perkembangan Kognitif dan Sosial Siswa - Nurhana, Nurhana; Suradi, Suradi; Danial, Danial (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the application of Vygotsky’s theory in mathematics learning and its implications for the development of students’ cognitive and social abilities. The research method used is a literature review by examining various scientific articles, books, and relevant academic sources. The focus of the study is directed toward the concepts of the Zone of Proximal Development (ZPD), scaffolding, social interaction, and the role of language in the process of learning mathematics. The findings indicate that the application of Vygotsky’s theory is able to enhance students’ conceptual understanding, critical thinking, and problem-solving skills through collaborative learning and gradual guidance from teachers and peers. In addition, the use of social context and mathematical communication has proven effective in building students’ knowledge structures in a more meaningful way. Thus, the application of Vygotsky’s theory in mathematics learning can serve as a strategic approach to improving the quality of both the learning process and student outcomes. This study is expected to serve as a reference for educators in designing mathematics learning based on social constructivism.   Keywords: Vygotsky’s Theory, Mathematics Education, ZPD, Scaffolding, Social Constructivism